Islamic Boarding School Management in the Digital Era: Integrating Tradition and Innovation in Islamic Education - Ach Syaikhu; Dukan Jauhari Faruq (FALASIFA : Jurnal Studi Keislaman, 2025)
This article aims to analyze Islamic boarding school management in the digital era, emphasizing the integration of Islamic boarding school traditions and technological innovation. The research employed a qualitative approach with a literature review method, using data sources consisting of journals, books, proceedings, and official documents published between 2018 and 2025 on Islamic boarding school management, digitalization, and Islamic education. The data were analyzed using content analysis techniques through the stages of reduction, categorization, and synthesis. The study results indicate that Islamic boarding school digitalization has had a significant impact on administrative efficiency, data transparency, and increased student participation. Furthermore, digitalization strengthens human resource capacity and supports students' digital literacy through various innovations, such as the Santri App. However, emerging challenges include limited infrastructure, gaps in human resource competencies, and the risk of fading Islamic boarding school traditions. The discussion emphasizes that digitalization should not be viewed solely as technical modernization, but rather as a long-term managerial strategy aligned with the Islamic boarding school's identity. Therefore, kiai leadership is required to play a visionary role in combining efficiency, strengthening literacy, and character education while preserving tradition. study concludes the need for an integrative management model for digital Islamic boarding schools that can harmonize tradition and modernization. Further research is recommended, highlighting empirical case studies of Islamic boarding schools that have implemented digital leadership and literacy programs